Four-layer nanocomposite structure as an effective optical waveguide switcher for near-IR regime. (3rd October 2016) - Panyaev, I S; Dadoenkova, N N; Dadoenkova, Yu S; Rozhleys, I A; Krawczyk, M; Lyubchanskii, I L; Sannikov, D G
Abstract: We present a theoretical study of the dispersion and energy properties of the eigenwaves (TE- and TM-modes) in a four-layer structure composed of a magneto-optical yttrium iron garnet guiding layer on a dielectric substrate covered by a planar nanocomposite guiding multilayer. The bigyrotropic properties of yttrium-iron garnet are taken into account for obtaining the dispersion equation and an original algorithm for the guided modes identification is proposed. We demonstrated the polarization switching of TE- and TM-modes dependent on the geometrical parameters of the guiding layers. The dispersion diagrams and field profiles are used to illustrate the change of propagation properties with variation of the multilayer thickness ratio of the nanocomposite's layers. The energy flux distributions across the structure are calculated and the conditions of the optimal guiding regime are obtained. The power switching ratio in the waveguide layers of about 6 dB for the wavelength range of 100 nm is shown to be achieved.